1997
DOI: 10.1007/bf01709258
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of isolates recovered from multiple sites of the nasopharynx of children colonized by nontypeableHaemophilus influenzae

Abstract: To determine whether the nasopharynx of children is colonized by a single or multiple strains of nontypeable Haemophilus influenzae, cultures were obtained from six nasopharyngeal sites in five children. For each child, all isolates yielded identical polymerase chain reaction fingerprints. The results indicate that these children were colonized in the nasopharynx with a single strain of nontypeable Haemophilus influenzae at one time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Forty-four percent of the children were colonized on one or more occasions, and the acquisition rate was greatest in the first year. Colonization mainly involves a dominant strain which can be followed by a series of other strains (1,9,15,24). The level of carriage varies according to different factors, i.e., age, siblings, and living conditions.…”
mentioning
confidence: 99%
“…Forty-four percent of the children were colonized on one or more occasions, and the acquisition rate was greatest in the first year. Colonization mainly involves a dominant strain which can be followed by a series of other strains (1,9,15,24). The level of carriage varies according to different factors, i.e., age, siblings, and living conditions.…”
mentioning
confidence: 99%
“…Analysis of isolates recovered from 6 different sites in the nasopharynx of 5 children undergoing adenoidectomy revealed that each child harbored a single strain of H. influenzae in the nasopharynx [8]. In contrast, analysis of isolates from the nasopharynx of Australian aboriginal children in a population that is heavily colonized by H. influenzae showed that most children harbored multiple strains [14,15].…”
Section: Discussionmentioning
confidence: 95%
“…Each isolate of H. influenzae grown from a single colony from the original plate was analyzed by polymerase chain reaction (PCR)-based genomic DNA typing, as described elsewhere [7,8]. In brief, 3 colonies were suspended in 0.1 mL of sterile water and centrifuged at 14,000 g for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Many commensal strains of pathogens that are present in the nasopharynx have potential pathogenicity [33]. The nasopharynx of children with AOM could have been colonized by an aggressive strain that replaced the benign commensal strain and progressed to causing infections in the middle ear.…”
Section: Discussionmentioning
confidence: 99%